Application of natural coating improves the conservation of cut carnation flower - Pinzetta Junior, José S. [UNESP]; Mattiuz, Claudia F. M.; Sillmann, Thaís A.; Junior, Bene Mauricio Baglioni [UNESP]; Inestroza-Lizardo, Carlos; Mattiuz, Ben-Hur [UNESP] (My University, 2023)
Carnation (Dianthus caryophyllus) is one of the most important and popular cut flowers for the ornamental industry. However, it has a short decorative life, being water loss one of the main challenges. Water loss leads the petals to wither with a consequent loss of its commercial value. One of the techniques used in postharvest technology is the use of coatings and films, which interfere in gas exchange and water loss, maintaining the quality of cut flowers. The current study investigated the effects of a natural coating based on hydroxypropyl methylcellulose (HPMC) at 5% and beeswax (BW) in cut carnation flower cv. Delphi stored at 20°C and 70% RH. The application of HPMC + 40% BW treatment in flowers resulted in 30% higher fresh weight, 17% higher relative water content (RWC) and 80% higher flower opening compared to untreated flowers. The shelf life of untreated and HPMC + 40% BW carnations was 7 and 12 days, respectively, allowing a shelf-life extension of up to five days.
A aplicação de película natural melhora a conservação de flores de corte de cravos
Keywords: beeswax; cut flower; Dianthus caryophyllus; flower quality; hydroxypropyl methylcellulose; shelf-life extension